What do talents want? Work expectations in India, China, and Germany - Marlene Walk; Heike Schinnenburg; Femida Handy (Zeitschrift für Personalforschung (ZfP), 2013)
International talent management becomes increasingly important, because companies compete on a global scale for qualified employees. Finding highly educated talent, however, is difficult, especially in the Asia-Pacific region. This research investigates the work expectations of Chinese (N=404), Indian (N=588), and German (N=257) students, the talent group from which companies hope to recruit their future workforce. Incorporating their specific expectations is essential; if these expectations are not met, decreases in job satisfaction, commitment, and performance are likely. Using factor analytic techniques, we develop a scale that reliably measures students' work expectations. A two-factor structure was established and generality was assessed across countries, age, gender, and study level. Findings show that students from all countries share more similarities than cultural differences might predict. Nevertheless the subtleties provide essential insights for international talent management and call for more targeted recruitment and retention strategies. – – Internationales Talentmanagement gewinnt zunehmend an Bedeutung, da Unternehmen in einem globalen Wettbewerb um qualifizierte Mitarbeiter stehen. Diese Studie befasst sich mit den Arbeitserwartungen von chinesischen (N=404), indischen (N=588) und deutschen (N=257) Studierenden - der Gruppe, aus der Unternehmen ihre zukünftigen Arbeitskräfte rekrutieren. Die Einbeziehung spezifischer Arbeitserwartungen ist vor allem für qualifizierte Talente notwendig. Sollten ihre Arbeitserwartungen nicht erfüllt werden, ist eine Verringerung von Arbeitszufriedenheit, Commitment und Arbeitsleistung wahrscheinlich. Unter der Verwendung von faktoranalytischen Methoden wird in diesem Artikel ein Erhebungsinstrument entwickelt, welches studentische Arbeitserwartungen reliabel misst. Die Ergebnisse zeigen, dass Studierende aus allen Ländern mehr Gemeinsamkeiten aufweisen, als kulturelle Unterschiede vermuten lassen. Dennoch bieten die festgestellten Besonderheiten wichtige Einblicke für internationales Talentmanagement und fordern gezielte Rekrutierungs- und Bindungsstrategien.
Keywords: M10; M12; M16; J24; 650; talent management; China; India; Germany; work expectations; students